The Development of Psychometric Instrument on Religiosity Among Entrepreneurs: An Early Analysis on Requirements and Etiquettes Based on Islamic Worldview - Abdul Hamid, Solahuddin; Ishak, Mohd Sobhi; Abdul Rahman, Mohd Nizho; Sa'ari, Che Zarrina; Borhan, Joni Tamkin; Md Zain, Azman (Serials Publications, 2017)
The study of religious experience is a complex process because it involves ideology, admiration, the relationship with the supernatural, religious practice and participation in religious institutions and communities relationship. Logical and empirical truth solely is certainly not possible to analyze the level of religious practice (religiousity) completely. However, empirical approach is useful for understanding the relationship between religious practice and the various psychological attribution and prove that the practice of Islamic values in business activity was not among the reasons for failure, otherwise neglect was one of the reasons entrepreneurs fail in their business. Description of this article will focus on the question of theoretical concept is based on the standards set by the Qur’an and Hadith and Islamic intellectual scene in order at least one day there is the ability to form not only of thought, even the discipline psychometric itself based on ethic in Islamic worldvie